Reducing complications of femoral neck fracture management: a retrospective study on the application of multidisciplinary team - Weiming Liang; Gang Qin; Lizhi Yu; Yingying Wang (BMC Musculoskeletal Disorders, 2023)
Abstract Background Femoral neck fractures are associated with substantial morbidity and mortality for older adults. Multi-system medical diseases and complications can lead to long-term care needs, functional decline and death, so patients sustaining hip fractures usually have comorbid conditions that may benefit from application of multidisciplinary team(MDT). Methods This is a retrospective cohort study that incorporates medical record review with an outcomes management database. 199 patients were included who had surgery for a new unilateral femoral neck fracture from January 2018 to December 2021 (96 patients in usual care (UC) model and 103 patients in MDT model. High-energy, pathological, old and periprosthetic femoral neck fracture were excluded. Age, gender, comorbidity status, time to surgery, and postoperative complication, length of stay, in-hospital mortality, 30-day readmission rate, 90-day mortality data were collected and analyzed. Results Preoperative general data of sex, age, community dwelling and charlson comorbidity score of MDT group (n = 103) have no statistically significant difference with that of usual care (UC) group. Patients treated in the MDT model had significantly shorter times to surgery (38.5 vs. 73.4 h;P = 0.028) and lower lengths of stay (11.5 vs. 15.2 days;P = 0.031). There were no significant differences between two models in In-hospital mortality (1.0% vs. 2.1%; P = 0.273), 30-day readmission rate (7.8% vs. 11.5%; P = 0.352) and 90-day mortality (2.9% vs. 3.1%; P = 0.782). The MDT model had fewer complications overall (16.5% vs. 31.3%; P = 0.039), with significantly lower risks of delirium, postoperative infection, bleeding, cardiac complication, hypoxia, and thromboembolism. Conclusion Application of MDT can provide standardized protocols and a total quality management approach, leading to fewer complications for elderly patients with femoral neck fracture. Trial registration No.